Correlation of non-physically work environment, employee and work engagement to contract employee turnover intention in Bekasi - Purwanti Purwanti; Rismawati Rismawati (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
Observing problems in the industrial world, one of which is employee turnover such as layoffs resignation, employee turnover is a severe problem faced by companies that have to incur a lot of costs and losses, so researchers feel interested in conducting research by highlighting the correlations of work engagement, employee engagement, and non-physical Work Environment Impacts Turnover Intention of Contract Employees in the Jababeka Area. This study aims to determine the correlation between work engagement, employee engagement, and non-physical work environment on turnover intention, especially in the Jababeka area, Cikarang Bekasi. This study uses the probability sampling method, which provides equal opportunities for each element (member) of the population to be selected as a sample member. The sample studied is part of the contract employees in the Jababeka area, with as many as 90 respondents. The data type used is primary data, and this study uses a data processing tool in the form of the SmartPLS (Partial Least Square) program to test the hypothesis. The results of this study indicate a significant effect of Employee Engagement on Contract Employees' Turnover Intention and a substantial effect of Work Engagement on Contract Employees' Turnover Intention. However, the Non-Physical Work Environment does not affect Contract Employees Turnover Intention in Bekasi.